Impact of Low Procalcitonin Results on Antibiotic Administration in Hospitalized Patients at a Tertiary Care Center. Issue 2 (June 2016) - Brennan, Meghan; Osterby, Kurt; Schulz, Lucas; Lepak, Alexander
Abstract Procalcitonin is a sensitive and specific marker of bacterial infection; low results allow clinicians to safely de-escalate antibiotics. This retrospective cohort study aimed to determine the effect of low procalcitonin results on withholding, discontinuing, or de-escalating antibiotics in hospitalized patients at a tertiary care center. Antibiotics were initiated or continued without de-escalation in 55% of patients with low procalcitonin results. Among patients with low procalcitonin results, the primary service, but not measures of patient complexity, disease severity, or underlying disease process (lower respiratory tract infection evaluation versus systemic inflammatory response syndrome/possible sepsis) was associated with initiation or continued broad-spectrum antibiotic use. Provider-level factors may be an important variable in the initiation or continued use of broad-spectrum antibiotics for patients with low procalcitonin levels.